2021
DOI: 10.1155/2021/2935507
|View full text |Cite
|
Sign up to set email alerts
|

Bonding Performance for Repairs Using Bulk Fill and Conventional Methacrylate Composites

Abstract: This study compared the bond strength of a composite repair made with a bulk fill composite and a conventional one using different surface treatments. Specimens were prepared as truncated cones (bases: 4 mm × 2 mm, height: 4 mm) using a bulk fill (OBFa: Filtek One) or a conventional resin (FTKa: Filtek Z250) (n = 66). They were artificially aged (10,000 cycles, 5°C–55°C, 30 sec) and subdivided according to surface treatments: NT—no treatment (control), Abr—abrasion with a diamond tip, and sand—sandblasting wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(64 reference statements)
1
1
0
Order By: Relevance
“…This finding is rather interesting considering the general recommendation to use the same material in repairs, based on past studies with conventional composites only. Moreover, studies have shown long-term problems such as recurrent caries and fractures in repairs using nanoparticulate composites [11,12]. Similar results were reported by Koc-Vural et al [13], showing that the combination of bulk fill composites with conventional composites was superior to repairs with similar composites.…”
Section: Discussionsupporting
confidence: 64%
“…This finding is rather interesting considering the general recommendation to use the same material in repairs, based on past studies with conventional composites only. Moreover, studies have shown long-term problems such as recurrent caries and fractures in repairs using nanoparticulate composites [11,12]. Similar results were reported by Koc-Vural et al [13], showing that the combination of bulk fill composites with conventional composites was superior to repairs with similar composites.…”
Section: Discussionsupporting
confidence: 64%
“…This unevenness in stress concentration can initiate a crack that propagates within the substrate/resin composite/bonding interface and cause monolithic fractures [ 19 , 20 ]. Nevertheless, several studies pertinent to the repair bond strength to resin composites have employed the SBS test [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%